Stabilization by chemical preservatives of carboxymethyl cellulase from fungus Aspergillus niger produced by State Solid fermentation in fruit residues using chemical preservatives - Junqueira , Letícia Lima; Costa, Floriatan Santos; Franco, Marcelo; Assis, Sandra Aparecida de (Seven Editora, 2023)
The residues of fruticulture as acerola, guava, passion mango can be efficiently used to produce enzymes by Solid state fermentation. In this work we used these residues and filamentous fungus Aspergillus niger ATCC 1004 to obtain carboxymethyl cellulases (CMCase). The preservation of enzyme activity is a fundamental for provide commercial enzymes with good price and high enzyme activity. Three substances (sodium chloride, sodium benzoate and monosodium phosphate) were tested as enzyme activity preservative using a simplex-centroid mixture design was applied to obtain the better concentrations of this substances. The effect of preservatives was tested for 72 hours on the activity of the CMCase enzyme by incubating the enzyme with the salts of sodium chloride, monosodium phosphate and sodium benzoate at various concentrations, in citrate-phosphate buffer pH 5.0 at 50 mM, at a temperature of 50 °C. The results showed that the mixture that favored the optimum condition simultaneous response was composed of 42% sodium chloride, 38% sodium benzoate, and 20% monosodium phosphate. Then, the substances studied shows that are good option to preserve the CMCase enzyme produced fungus Aspergillus niger ATCC 1004. DOI:https://doi.org/10.56238/uniknowindevolp-054